2011
DOI: 10.1271/bbb.110055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chondroitin Sulfate and Its Oligosaccharides on Toll-Like Receptor-Mediated IL-6 Secretion by Macrophage-Like J774.1 Cells

Abstract: The effects of two types of chondroitin sulphate (CS), CS-A and CS-C, their oligosaccharides (oligo-CSs), and disaccharides (Di-CSs) on toll-like receptor (TLR)-mediated secretion of interleukin (IL)-6 were compared using macrophage-like cell line J774.1. IL-6 secretion in the J774.1 cells was markedly increased by Pam3CS4, LPS, and CpG, the ligands to TLR1/2, 4, and 9 respectively. Among these three ligands, CpG-induced IL-6 was most clearly suppressed by CSs and their digests. Suppression of IL-6 secretion b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
0
11
1
1
Order By: Relevance
“…On the other hand, considering the influence of the position of a sulfate group in the CS backbone on this GAG‐binding properties, the accessibility of these groups for binding should also be taken into account. It is commonly accepted that in a hydrated environment, the CS chains assume a helical conformation with the 6‐ O ‐sulfated groups that are localized peripherally and the 4‐ O ‐sulfated ones that lie near the midline of the polymer . Thus, the former groups are more accessible to ligands compared to the latter ones.…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, considering the influence of the position of a sulfate group in the CS backbone on this GAG‐binding properties, the accessibility of these groups for binding should also be taken into account. It is commonly accepted that in a hydrated environment, the CS chains assume a helical conformation with the 6‐ O ‐sulfated groups that are localized peripherally and the 4‐ O ‐sulfated ones that lie near the midline of the polymer . Thus, the former groups are more accessible to ligands compared to the latter ones.…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 99%
“…By contrast, experiments with a knockout and overexpression of C6ST‐1 revealed that 6‐ O ‐sulfated CS can alleviate a clinical manifestation of the disease . It has also been shown that C‐6‐S inhibited the in vitro secretion of IL‐6 in macrophages, which were proinflammatorily stimulated with CpG via Toll‐like receptor (TLR) 9, more effectively than C‐4‐S . Notably, the impact of CS on macrophage activity can be a crucial issue in the development and progression of a tumor as these cells are responsible for creating and maintaining the protumor–antitumor balance.…”
Section: The Role Of C‐6‐s In the Tumor Nichementioning
confidence: 99%
See 1 more Smart Citation
“…HMOSs and other NDOSs have been reported to bind to specific receptors on cells of the immune system as summarized by Georgi et al (88) and others (90,(131)(132)(133). Furthermore, in vitro evidence has been obtained for the epithelial transport of HMOSs (131).…”
Section: The Modulation Of Early-life Microbiota Correlates With Imprmentioning
confidence: 99%
“…In order to defend the host against invading pathogens, macrophages possess a broad range of receptors and are able to differentiate self from non-self through the recognition of pathogen-associated molecular patterns [3]. Several of these receptors are known to react to oligosaccharides [54,55]. Studies have also shown that the activation of macrophages may lead to the faster clearance of Salmonella [18,56].…”
Section: Intracellular Clearance Of Salmonella Enteritidis In U-937 Mmentioning
confidence: 99%